Spectrophotometric demonstration of the antibacterial property of tin chloride dihydrate (SnC12 2H20), a corrosion product in amalgam - Mercado, Faustino
Amalgam restorations develop a seal with time. Among the elements found in the dental material-tooth interface is tin which can be found in conjunction with chlorine forming a substance, SnCl2 2H2O. This study aims to investigate the possible antimicrobial roles of SnCl2 2H2O. Using spectrophotometry, bacterial density was determined in anaerobic glucose broth cultures of Streptococcus mutans, the organism implicated in the formation of dental caries. It was found that the addition of SnCl 2 2H2O (.2 mg/ml) on the culture medium inhibited the growth of Streptococcus mutans while growth followed the normal exponential increase in the cultures without SnCl2 2H2O. These results which were analyzed to be statistically significant by ANOVA (.01 level of significance) point to the conclusion that the presence of the corrosion product SnCl2 MgQ on the amalgam-tooth interface significantly prevents the recurrence of caries. This study was financially assisted by Sanofi-Winthrop, Inc.